New low-energy heating system.
Space heating and 'Domestic hot water' (DHW) in residential and commercial buildings are responsible for about 40 percent of total energy consumption in the EU. Meanwhile, solar thermal energy stands as one of the most promising heat sources available. Although energy efficiency in new buildings is important, the main target is existing buildings, due to the need for new developments and adaptation to existing technologies in order to comply with recent EU directives.